Analysis of antioxidation behavior of cryo-milled oxide-dispersion-strengthened ferritic steel incorporated with formation of Y–Ti–O(N) nano-precipitates. (15th February 2022) - Shin, Won-Sang; Baik, Sung-Il; Seidman, David N.; Lee, Kee-Ahn; Park, Changkyoo; Kim, Yoon-Jun
Abstract: Oxide-dispersion-strengthened steel were produced by mechanical alloying with milled Y2 O3 powder in a ball mill at room temperature (ODS-RT) and at -150 ℃ (ODS-LT). Both samples were exposed to air for 6000 h at 800 ℃ for examining their long-term oxidation resistance at a high temperature. After long-term exposure both samples showed subsurface degradation occurred concurrently such as internal precipitation, phase formation, and phase dissolution. It was associated with scale formation including a large number of short-circuit diffusion paths, which led to the rapid formation of a dense and stable protective oxide film in the initial oxidation stage. The resulting oxide scaling kinetics were more sluggish for ODS-LT compared with ODS-RT. A correlative characterization method involving transmission electron microscopy and atom probe tomography was used to determine factors affecting different oxidation kinetics. Nano-precipitate (NP) analysis showed that Y–Ti–O NPs were present at the grain boundaries of ODS-RT and that ODS-LT contained Y–Ti–O(N) NPs and a sub-micrometer-sized TiN precipitate. An assessment of segregation phenomena along with interfacial energies calculated using the Gibbsian interfacial excess showed that the behavior of Y atoms played a key role in clustering, and segregation at the interfaces. The calculated partial radial distribution function of major constituents indicated that the NPs in the two alloys had different Y content. Excess Y atoms segregated at the matrix/oxide interface in ODS-LT inhibited oxide growth. Therefore, Y atoms can be considered as a controlling factor for the oxidation rate at high temperatures. Graphical abstract: Image, graphical abstract